Molecular expression, characterization and potential applications of a thermostable alkaline protease from Geobacillus thermoglucosidasius SKF4 - Dan, Allison Suleiman (2022)
Protease enzyme catalyses the breakdown of protein molecules into simpler units such as amino acids and peptides. Thermostable proteases are the appropriate enzyme that can be used in industrial processes that require high temperature such as detergent, leather processing etc. Many thermostable proteases have been isolated, but only a few that are both alkaline stable and extremely thermostable have been cloned, completely characterized, and their potential industrial applications fully exploited. The main objective of this research was to clone a thermostable alkaline protease from a thermophilic bacteria and its potential applications as detergent additive, in the production of bioactive peptides and recovery of silver from X-ray film evaluated. In this study a new thermophilic bacterial that produces thermostable protease enzyme was successfully screened and identified using 16S rRNA gene sequence with 99 % identity with other members of Geobacillus sp. The organism which was isolated from hot spring in Sungai Klah Perak in Malaysia was identified as Geobacillus thermoglucosidasius SKF4 and was characterized using different parameters. The organism was highly thermophilic and produced protease enzyme at optima pH 7 and temperature of 60 oC. A thermostable alkaline serine protease SpSKF4 gene from the G. thermoglucosidasius SKF4 was amplified using polymerase chain reaction (PCR). The gene analysis showed an open frame of 1206 bp coding for a protein of 401 amino acids. The cloned gene was successfully expressed in Escherichia coli by T7 promoter using the pEASY® Blunt-end E1 prokaryotic expression vector. The sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) analysis of the protein revealed a mature protein of approximately 28 kilo Dalton (kDa) which was also confirmed by the western blot. Optimisation of SpSKF4 protein for soluble expression under different cultural conditions revealed an increase in expression and activity (200 U/mL) at isopropyl β-D thiogalactoside (IPTG) concentration of 0.4 mM and a temperature of 20 ºC after 12 h incubation. The recombinant alkaline serine protease was partially purified and fully characterised. The partially purified enzyme was active between 20-100 ºC with optimum activity (353 U/mL) at optima pH 10 and temperature of 80 ºC. Its activity was stable at about 40 % capacity at optimum pH 10 and 80 °C after 24 h incubation, with half-life of 15h. Its activity was increased by 60 % with the addition of 10 mM Ca2+ and also addition of Mg2+ increased the activity by 30 % at concentration of 2.5 mM. However, the activity was reduced by 30 % by copper, a heavy metal. The protease enzyme SpSKF4 was stable in surfactants such as Sodium dodecyl sulphate (SDS). The SDS however, increased the activity of the enzyme by 20 %. The enzyme was inactivated (100 %) by phenylmethylsulfonyl fluoride (PMSF) at concentration of 10mM indicating the enzyme was a serine protease. The kinetic study showed high catalytic efficiency (Kcat/Km) (4.9 mg/ml/min) with casein at 80 oC, with Vmax and Km of 7.1 U/ml and 0.57 mg/ml, respectively. The recombinant enzyme was highly stable in organic solvents and certain oxidising and reducing agents, and also showed high stability (> 90 %) with some commercial detergents. The enzyme showed high capacity as a potential industrial enzyme as a detergent additive, in the recovery of silver from X-ray film and in the production of anti-microbial and anti-oxidant peptides from proteins hydrolysates. The hydrolysates produced from casein and Bovine Serum Albumin (BSA) using SpSKF4 protease showed high 2,2-diphenyl-1-picrylhydrazyl (DPPH) (> 67 %) and 2,2-azino-bis3-ethylbenzothiazoline-6-supfonic acid (ABTS) (> 85 %) radicals scavenging activities. The Fe2+ chelating capacity was about 85 %. These have confirmed that the thermostable protease enzyme from G. thermoglucosidasius species from hot spring could be used as industrial enzyme in various capacities. In conclusion, a thermostable SpSKF4 protease gene was successfully cloned from a thermophilic organism G. thermoglucosidasius SKF4 isolated from hot spring and the enzyme showed a remarkable potential as a prospective enzyme for industrial and biotechnological applications.